Echoes in the Field - Fotić, Jelisaveta (Svetovi (Ljubljana), 2026)
This article examines the deaths of elderly interlocutors after ethnographic research on dia-betes in Belgrade. From the author’s dual position as an anthropologist and a person with diabetes, it argues that grief and mortality are not disruptions but analytical events integral to ethnography. Reframing loss in this way advances medical anthropology’s engagement with chronicity and death, while exposing the structural neglect embedded in biomedical individualism.
Keywords: angažirana antropologija; Antropologija; Biomedicina; čustveno delo; diabetes; emotional labour; engaged anthropology; Etnologija; grief; interlocutor death; medical anthropology; Medicinska antropologija; refleksivnost; reflexivity; Sladkorna bolezen; Smrt; smrt sogovornikov; Žalovanje